SURAT KAPAL DALAM PERKAWINAN ADAT MELAYU RENGAT DI DESA ALANG KEPAYANG KECAMATAN RENGAT BARAT INDRGAIRI HULU - Yulihasman "; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research entitled "Letter Ships In Marriage Adat Rengat In Rural Village Alang Kepayang Rengat West Indrgairi Hulu". The research was conducted in Alang Village, Indragiri Hulu District, which aims to find out what the meaning of Tradition of Letter of Ship and the changes in it. The method used in this research is descriptive qualitative research method, the discussion of this research is presented and analyzed in the form of description of words (description) with a qualitative approach. This research is also supported by the implementation of activities wawan way in depth to the informants (informants) that have been established in advance by the researchers. From the results of interviewing way obtained information that is very supportive to the esahan from the data that became the focus of this research. Based on the results Research, in this tradition can be some important things that are divided into two implementation of Tradition Letter Ship itself, namely: Syair Letter ships is a series of seloka is a poem and rhyme, which contains a story about meeting two souls to marriage, personal introduction Brothers near the bride, religious advice, prayer and hope in married life. Literary works belonging to the Malay community in Indragiri. "Syair Surat Kapal '' a poem that has existed since ancient, this poem is passed down to the descendants of the Indragiri Kingdom Age to the present Syair Surat Kapal is a long poem made by our datok in Indragiri.Keywords: Letter Ship, Customs, and changes